Evidence for the Influence of School Context on College Access - Strick, Betsy R. (Education Policy Analysis Archives, 2012)
Since the release of the Coleman Report in 1966, studies (such as Sirin, 2005; Radford, Berkner, Wheeless, and Shepherd, 2010) have continued to find an association between socioeconomic status and educational attainment. Wyner, Bridgeland, and Diiulio (2007) observe that a progressively lower proportion of low-income, high achieving students remain successful as they advance from elementary school through college. The present study considers college enrollments from a college preparatory charter secondary school serving low-income students. The study finds that alumni enrolled in four-year colleges at a higher rate than did lottery-assigned comparison students. These four-year college enrollment findings held for Hispanic, African American, and Asian American students. At the same time, the overall college enrollment rates, meaning enrollment in two- and four-year colleges in contrast to no college enrollment, were quite similar for the Preuss School and comparison students. These results were achieved, this study suggests, through numerous academic and social supports that increase college eligibility rates and institute four-year college and financial aid applications as part of coursework. The four-year college enrollment findings offer the promise that schools can be arranged to increase academic opportunities for low-income students.